Growth of the Symbiotic Fungus of the Grass-cutting Ant Atta capiguara (Hymenoptera: Formicidae): Effect of Grass Extracts - Castellani, Maria A.; Forti, Luiz Carlos [UNESP]; Fenille, Roseli C.; Raetano, Carlos Gilberto [UNESP]; Moreira, Aldenise A.; Andrade, Ana Paula P. [UNESP]; Camargo, Roberto S. [UNESP]; Lemos, Raimunda N. S.; Aguiar, Aline G.; Nagamoto, Nilson S. [UNESP] (California State University, 2009)
The objective of this study was to evaluate the influence of grass extracts on growth of the symbiotic fungus of Atta capiguara (Hymenoptera: Formicidae: Attini), in order to obtain support information on control strategies against this pest. The radial growth of the in vitro cultivated symbiotic fungus was evaluated in the following bioassays: 1) extracts at a single concentration: leaves of Pennisetum purpureum cv. Cameron, Hyparrhenia rufa, Brachiaria brizantha cv. Marandu, Saccharum officinarum variety SP80-1842, and Paspalum spp.; 2) effect of different extract concentrations: grass extracts from bioassay 1 were prepared at concentrations of 0.25, 0.50, 1.00, and 2.00% (w.v(-1)); 3) effect of plant age and pH in the medium: this was conducted for S. officinarum only. Culture media containing B. brizantha are detrimental to growth of the symbiotic fungus of A. capiguara. Culture media containing . rufa, P. purpureum, or Paspalum spp. do not affect fungal growth, and produce growth similar to the one obtained in PDA medium without extract (control). No extract concentration effects were observed. Medium pH is an important factor in determining the effects of S. officinarum extracts on growth of the symbiotic fungus of A. capiguara.
Keywords: Attini; Brachiaria; extract; Hyparrhenia; Paspalum; Pennisetum; Saccharum